DETERMINANT SERVICE PERFORMANCE THROUGH MOTIVATION ANALYSIS AND TRANSFORMATIONAL LEADERSHIP - Bastari, Ary (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze: 1) the effect of transformational leadership on motivation on the employees of the Regional Development Bank of South Kalimantan. 2) the effect of motivation onperformance service on South Kalimantan Regional Development Bank employees. 3) the effect of transformational leadership onperformance service in South Kalimantan Regional Development Bank employees. The research method is: quantitative research using a survey method in question is to explain the influence or causal correlation which is called by the path analysis(pathanalysis). The respondents were 199 employees at the South Kalimantan Regional Development Bank. The results of the study are: 1) the influence of transformational leadership on motivation at the Regional Development Bank of South Kalimantan 2) the influence of motivation on service performance at the Regional Development Bank of South Kalimantan. 3) the influence of transformational leadership on service performance at the South Kalimantan Regional Development BankKeyword--,